Ecotoxicidade de esgoto tratado como um parâmetro operacional em ETES - Almeida, Gabriela Cristina Fonseca; Umbuzeiro, Gisela de Aragão (International Workshop for Innovation in Safe Drinking Water, 2022)
Aquatic ecosystems are used as destination of urban effluents. According to Brazilian regulation, final effluents must not have the potential to cause impact on the receiving body and, to assess this impact, toxicity tests are required. The objective of this work was to evaluate the acute toxicity with Daphnia similis and chronic with Ceriodaphnia dubia of final effluents from 4 sewage plants (ETEs, named A, B, C and D) from Campinas, SP, Brazil, with different treatments’ levels. Six monthly campaigns were carried out in 2022 and samples were collected before and after chlorination. The effluents from ETE B showed acute toxicity in all campaigns, and effluents from ETE A and C showed acute toxicity in at least one campaign, but with low toxicity (EC50, 48h >50%). Chronic toxicity was detected in all effluents, except in ETE D (reuse water production station) indicating the great efficiency of the treatment of membrane bioreactors (MBR). Acute tests with fish embryos (FET) will be performed to compare the results of tests with cladocerans. The evaluation of the impact potential of the effluents will also be carried out based on the average of effluent discharges and in reference to the respective receiving bodies.